1982
DOI: 10.1148/radiology.145.3.7146394
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic detection of complications following umbilical arterial catheterization in the neonate.

Abstract: Seventy-one neonates with umbilical arterial catheters received serial real-time ultrasound examinations in order that the identification and natural history of catheter-associated thrombosis could be prospectively evaluated. Twelve (17%) of the infants had clinically evident signs of vascular compromise. Ultrasound detected abnormal intravascular echoes or lack of expansile pulsation in 10 of these 12 (83%). Abnormal echogenic foci were consistent with thrombus and intimal dissection. Two infants without clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
3

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 0 publications
1
14
0
3
Order By: Relevance
“…21,22 Ultrasound scan has been used successfully to identify large vessel thrombus. 5,26 It is a safe, readily available test that can be done at the bedside. As umbilical catheters (UCs) have a relatively high incidence of associated thrombosis, we hypothesized that having one or more of these genetic prothrombotic mutations (FVL, PTm and/or MTHFR) would increase the risk of UC-associated thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Ultrasound scan has been used successfully to identify large vessel thrombus. 5,26 It is a safe, readily available test that can be done at the bedside. As umbilical catheters (UCs) have a relatively high incidence of associated thrombosis, we hypothesized that having one or more of these genetic prothrombotic mutations (FVL, PTm and/or MTHFR) would increase the risk of UC-associated thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…A simple, noninvasive method to examine the aorta in neonates for thrombosis by using real-time sonography has been recently described by Oppenheimer and others [2][3][4]. We undertook a study to (1) determine the frequency of umbilical-artery-catheter thrombosis, (2) examine risk factors for it, (3) define the associated mortality and morbidity, (4) …”
mentioning
confidence: 99%
“…2,5 It has been reported that 1% of newborn infants with catheters have symptoms indicative of thrombosis, 6 and it is estimated that the incidence of catheter-associated asymptomatic thrombosis is 20-30%. [7][8][9][10][11] An adequate management of thrombosis is generally complicated due to the extrapolation of adult management techniques. However, over the past years, major differences related to age have been observed in this condition (epidemiology, diagnostic tests, pharmacokinetics of antithrombotic agents), which have favored the use of diagnostic and therapeutic procedures appropriate for this period in life.…”
Section: Introductionmentioning
confidence: 99%